Siklus dan Terjadinya Menstruasi Serta Pandangan Islam di Dalamnya - Sumartini, Titin (Musawa Jurnal Studi Gender dan Islam, 2007)
Women have experiencedvarious discriminationsin most part of humans' history. We have witnessed violence against women portrayed and reported through mass media. Such violence also occurs in Muslim states, including Indonesia. Surprisingly there is also violence against women committed on the basis of their biological realities, namely monthly period. Menstruation has been conceptualized a curse for women so that they feel and endure the consequences of the primordial sin committed by Eve 'the symbolic woman'. This article will argue that such understandingof menstrual taboo is rooted in ancient story, and not from Islamic teaching.